2012
DOI: 10.1016/j.ceb.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of BMP activity and range in Drosophila wing development

Abstract: Bone morphogenetic protein (BMP) signaling controls development and maintenance of many tissues. Genetic and quantitative approaches in Drosophila reveal that ligand isoforms show distinct function in wing development. Spatiotemporal control of BMP patterning depends on a network of extracellular proteins Pent, Ltl and Dally that regulate BMP signaling strength and morphogen range. BMP-mediated feedback regulation of Pent, Ltl, and Dally expression provides a system where cells actively respond to, and modify,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 68 publications
0
43
0
Order By: Relevance
“…For example, the adult wings develop from wing imaginal discs. During larval development, the bone morphogenetic protein homolog decapentaplegic (dpp) is expressed in a narrow band of cells anterior to the anteroposterior (A/P) compartment boundary (Figure 4B) (Raftery and Umulis, 2012). The dpp-expressing cells in the wing blade primordium contribute to tissues anterior to the A/P boundary in the adult wing blade (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the adult wings develop from wing imaginal discs. During larval development, the bone morphogenetic protein homolog decapentaplegic (dpp) is expressed in a narrow band of cells anterior to the anteroposterior (A/P) compartment boundary (Figure 4B) (Raftery and Umulis, 2012). The dpp-expressing cells in the wing blade primordium contribute to tissues anterior to the A/P boundary in the adult wing blade (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…In the adult, the wing that was developed from the illuminated wing imaginal disc indicated obvious loss of cells (Figures 4D, 4E, and S4). The cells between longitudinal veins 3 and 4 appeared to be lost; these cells are known to be descendant from the dpp-expressing cells in the wing blade primordium (Figure 4C) (Raftery and Umulis, 2012). On the other hand, the tissues developed from the dpp-non-expressing cells seemed normal including the longitudinal veins 1, 2, and 5, and the posterior cross vein.…”
Section: Resultsmentioning
confidence: 99%
“…They play critical roles in many cellular processes and in tissue homeostasis and development [6,7]. BMPs form a morphogen gradient that controls the dorsal-ventral patterning of invertebrate and vertebrate embryos [8,9]. Mouse genetic studies confirmed the essential roles for BMP-Smad1/5/8 signaling in early embryonic development and postnatal tissue homeostasis [7].…”
Section: Introductionmentioning
confidence: 83%
“…BMPs form a morphogen gradient that decides cell fates during early embryonic development [8,9,43]. In addition, BMP-Smad1 signaling controls many other aspects of development and tissue homeostasis and its dysregulation leads to the development of a number of diseases, including cancer and skeletal and vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest in the wing primordium are the GPI-linked Drosophila glypicans, Dally and Dally-like protein (Dlp), and two secreted molecules, Pentagone (Pent) and Larval Translucida (Ltl) that appear to provide a ‘BMP shuttle’ function while ensuring tight feedback controls (reviewed in [84]) (Figure 4). The ability of Dally to stabilize Dpp at the cell surface in trans , has led to a model by which BMPs are handed off from one cell to another in a series of glypican-BMP association-dissociations [85]**.…”
Section: Other Modes Of Moving Bmp Ligands In the Extracellular Spacementioning
confidence: 99%